Pengaruh kemampuan kerja dan motivasi kerja terhadap kinerja karyawan PT. Nusantara Card Semesta (NCS) cabang Jambi - Aditya Rachman; Zulfina Adriani; Dwi Kurniawan (Jurnal Dinamika Manajemen, 2019)
This study aims to: determine the description of work ability, work motivation and employee performance of PT. Nusantara Card Semesta (NCS) Jambi branch. As well as to determine the effect of work ability and work motivation of employees on the performance of employees of PT. Nusantara Card Semesta (NCS) Jambi Branch. Based on the results of the study that: 1) Description of the work ability of PT. Nusantara Card Semesta (NCS) Jambi branch with an average score of 106.5 is included in the very high category. The description of the average work motivation score of PT. Nusantara Card Semesta (NCS) Jambi Branch, which is 92.2, is included in the high category. Description of employee performance of PT. Nusantara Card Semesta (NCS) Jambi Branch with an average score of 99.1 is in the high category. 2) Based on the results of multiple linear regression testing that the variables of work ability and work motivation partially have a positive and significant effect on the performance of employees of PT. Nusantara Card Semesta (NCS) Jambi branch. Meanwhile, the variables of ability and work motivation also have a significant effect on the performance of employees of PT. Nusantara Card Semesta (NCS) Jambi branch.